The ORF8 protein of SARS-CoV-2 induced endoplasmic reticulum stress and mediated immune evasion by antagonizing production of interferon beta - Rashid, Farooq; Dzakah, Emmanuel Enoch; Wang, Haiying; Tang, Shixing (Virus research, 2021)
•SARS-CoV-2 orf8 genotypes, orf8L and orf8S induced ER stress pathways.•SARS-CoV-2 orf8 genotypes, orf8L and orf8S antagonized interferon Beta production.•SARS-CoV-2 orf8 genotypes, orf8L and orf8S decrease the nuclear translocation of IRF3 induced by poly (I:C).•The effects of orf8L and orf8S are in the context of ER stress pathways regulation and interferon Beta antagonizing were same. The open reading frame 8 (orf8) is an accessory protein of SARS-CoV-2. It has 121 amino acids with two genotypes, orf8L and orf8S. In this study, we overexpressed the orf8L and orf8S of SARS-CoV-2 as well as the orf8b of SARS-CoV to investigate their roles in the regulation of endoplasmic reticulum (ER) stress and the inhibition of interferon beta (IFNß) production. We found that the two genotypes of SARS-CoV-2 orf8 are capable of inducing ER stress without significant difference by triggering the activating transcription factor 6 (ATF6) and inositol-requiring enzymes 1 (IRE1) branches of the ER stress pathway. However, the third branch of ER stress pathway, i.e. the protein kinase-like ER kinase (PERK), was unaffected by the overexpression of SARS-CoV-2 orf8L or orf8S. Moreover, both orf8L and orf8S of SARS-CoV-2 are capable of down regulating the production of IFNß and interferon-stimulated genes (ISG), ISG15 and ISG56 induced by polyinosinic-polycytidylic acid (poly (I:C)). Moreover, we also found decreased nuclear translocation of Interferon regulatory factor 3 (IRF3), after overexpressing orf8L and orf8S induced by poly (I:C). Our data demonstrated that SARS-CoV-2 orf8 protein could induce ER stress by activating the ATF6 and IRE1 pathways, but not the PERK pathway, and functions as an interferon antagonist to inhibit the production of IFNß. However, these functions appeared not to be affected by the genotypes of SARS-CoV-2 orf8L and orf8S.